Pathological and clinical insights into DICER1 hotspot mutated Sertoli-Leydig cell tumors: a comparative analysis - Zhuoyao Lyu; Yilin Liu; Jingci Chen; Pengyan Wang; Zhaohui Lu; Xiaoyan Chang; Xianlong Chen; Heng Ma; Shengwei Mo; Shuangni Yu; Jie Chen (Diagnostic Pathology)
Abstract Background Sertoli-Leydig cell tumors (SLCTs) are a rare group of sex cord-stromal tumors that account for less than 0.5% of all ovarian tumors. This study aims to compare the pathological and clinical characteristics of SLCTs with and without DICER1 hotspot mutations, highlighting the impact of these genetic variations on clinical manifestation, prognosis, and pathological morphology. Methods A retrospective analysis was conducted on 50 SLCTs. DICER1 RNase IIIb hotspot mutations were detected by the Sanger sequence. Clinical information, such as patients' symptoms, tumor staging, prognosis, and pathological features, such as tumor differentiation and growth patterns, were collected. Results DICER1 mutation only appears in the intermediate/poorly differentiated SLCTs (35.7%), while none in the well-differentiated SLCTs. The patients with DICER1 mutation had a younger age of onset (17, 15–25) compared to the wild-type group (42, 27–58). Regarding pathological morphology, the mutant group showed a higher probability of having retiform components (40.0%) and cords or ribbon-like arrangement (33.3%). Besides, they exhibited mucinous edematous stroma (80.0%) and hemorrhage (80.0%) more frequently than the wild-type group. The mutant tumor had more mitotic figures. (11/10HPF), higher Ki-67 index (16.1%), and more CD20-positive cell infiltration. Patients of the mutant group were more likely to experience recurrence, and their tumors were more prone to rupture. Conclusions This study demonstrates that DICER1-mutant and wildtype SLCTs have marked differences in pathological morphology and clinical manifestation. DICER1-mutatant SLCTs display worse prognosis, higher proliferative activity, and potentially more active immune microenvironments, which underscores the importance of genetic testing in diagnosing and assessing the prognosis of SLCTs.